Average rate = [h(3) - h(0)]/(3 - 0)
h(3) = 300 - 16(3)^2 = 300 - 16(9) = 300 - 144 = 156
h(0) = 300 - 16(0)^2 = 300
average rate = (156 - 300)/3 = -144/3 = -48
Therefore, the object falls with an average rate of 48 ft/s during the first 3 seconds.
Answer:
d
Step-by-step explanation:
becuase 0.54166666666 is equal to it
Hey there!!
Recursive formula :
... a( n ) = a ( n - 1 ) + 7
The first term is 12
To find the second term, we will need to substitute 2 in place of ' n '
2 term :
... a( 2 ) = a ( 2 - 1 ) + 7
... a( 2 ) = a( 1 ) + 7
We know a( 1 ) = 12
... a( 2 ) = 12 + 7
... 19 is the second term and we will need to use this to find the other terms.
Hope my answer helps!
Answer:
43.
Step-by-step explanation:
Follow PEMDAS (Parentheses, exponents, multiply, divide, add, subtract). First you do 8-4 which is 4, then you multiply 4 by 4 which is 16 since you multiply next, then you add 27 to 16 which then gets you to 43.